(untitled) (Biological Sciences - PJSIR, 2002)
Biowaste materials were evaluated as metal ion adsorbents in aqueous medium. The biowastes used were black gram husk, wheat bran, sheesham (Dalbergia sissoo) sawdust, pea pod , rice husk and cotton and mustard seed cakes. All these biosorbents, except pea pod and rice husk, exhibited good adsorption potential for Cd, Pb, Cu, Zn and Ni. Black gram husk (bgh) was found to have the highest sorption capacity with 100, 99.4, 95.7, 98.2 and 93.1% removal of Cd, P_b, Cu, Zn and Ni, respectively. The metal ions adsorbed by bgh desorbed with 0.1 M HCl and the regenerated btosorbent was reused successfully for the sorption of metal ions in the next cycle. Concentration of the tested metals achieved at equilibrium in the contaminated aqueous medium was well below the maximum limits recommended by UNEP for sewage discharge. The study indicates the potential of bgh as a new, inexpensive and efficient biosorbent for the treatment of water contaminated with heavy metals.